NON-PHARMACOLOGICAL NURSING INTERVENTIONS FOR THE MANAGEMENT OF PRE-CESAREAN MATERNAL ANXIETY: A LITERATURE REVIEW - Widhiastuti, Ratna (Universitas Airlangga, 2025)
Background Preoperative anxiety before caesarean delivery remains a major clinical concern, adversely affecting maternal and neonatal outcomes. This review synthesizes evidence on the effectiveness of non-pharmacological nursing interventions in reducing maternal preoperative anxiety before caesarean section. Method Guided by the PRISMA 2020 framework, literature published between 2015 and 2025 was systematically searched in PubMed, ScienceDirect, and EBSCOhost. Eligible studies included randomized controlled trials, quasi-experimental, and cohort studies examining nursing-led, non-pharmacological interventions such as acupressure, aromatherapy, music therapy, guided imagery, relaxation, and structured education. Result Twelve studies met inclusion criteria. Interventions such as acupressure, aromatherapy, guided imagery, and preoperative education consistently reduced anxiety scores measured by validated instruments (e.g., STAI, HADS). Cultural adaptation enhanced intervention effectiveness, particularly in music-based therapies. Conclusion Non-pharmacological nursing interventions are effective, low-risk strategies for reducing maternal anxiety before caesarean delivery. Integrating culturally tailored, multimodal interventions into preoperative nursing care may optimize psychological and physiological outcomes.